Utilization of Picture Story Book about the Process of Rain in Learning IPAS Class IV SD Negeri 8 Menteng - Hasanah, Siti Fadillah; Afrom, Ichyatul; Manesa, FX. (Tunas: Jurnal Pendidikan Guru Sekolah Dasar, 2024)
The material in class IV IPAS learning about evaporating and condensing which is related to the process of rain. Students have difficulty in understanding the concept of rain if the teacher only explains with the lecture method without supporting media. Based on these problems, an effort to improve learning is needed, one of which is utilizing learning media to meet the needs of students. The utilization of picture storybook media is to describe in detail the utilization of picture storybooks about the process of rain in learning IPAS grade IV SDN 8 Menteng. This research was conducted using a qualitative approach. Data collection techniques through observation, interviews and documentation. Data analysis used analysis techniques proposed by Miles and Huber. The results of this study indicate the utilization of picture storybooks, students are interested in reading picture storybooks, students utilize picture storybooks well, students can remember the contents of rain picture storybooks, by reading rain picture storybooks students understand about the process of rain. The utilization of this picture storybook provides a good response and is accepted by students and has a good impact on supporting the learning process.